Modeling WWOX Loss of Function in vivo: What Have We Learned? - Tanna, Mayur; Aqeilan, Rami I. (Frontiers in Oncology, 2018)
The WW domain–containing oxidoreductase (WWOX) gene spans one of the most and highly expressed common fragile sites (CFS), FRA16D, which is known to be implicated in cancer. WWOX encodes a 46kDa adaptor protein, which contains two WW–domains at its N–terminus and a C–terminal catalytic domain homologous to short–chain dehydrogenase/reductase (SDR) family proteins. A high sequence conservation of WWOX orthologues from insects to rodents and ultimately humans suggest its significant role in physiology and homeostasis. Indeed, data obtained from several animal models including flies, fish and rodents demonstrate WWOX in vivo requirement and that its deregulation results in severe pathological consequences including growth retardation, post–natal lethality, neuropathy, metabolic disorders and tumorigenesis. Altogether, these findings set WWOX as an essential protein that is necessary to maintain normal cellular/physiological homeostasis. Here, we review and discuss the lessons and outcomes learned from modeling WWOX expression in vivo.